Hubungan Mutu Pelayanan Dengan Tingkat Kepuasan Pasien Rawat Inap Di Puskesmas Ponu Kabupaten Timor Tengah Utara Tahun 2022 - Maria D.S Manlea; Yoseph Kenjam; Yudishinta Missa (Yayasan Literasi Sains Indonesia, 2023)
Service quality is an element that can affect patient satisfaction while performing health services at the health center. Based on the results of interviews with 5 inpatients at Puskesmas Ponu, it was found that there was dissatisfaction with the services. This dissatisfaction indicates the poor quality of health center services. This study aims to determine the ratio of service quality to inpatient satisfaction in Puskesmas Ponu Kabupaten Timor Tengah Utara in 2022. This type of research is analytical with a cross-sectional study approach. The sample in this study consisted of 51 inpatients obtained by simple random sampling using probability sampling methods. Data collection was done through questionnaire quality health services and patient satisfaction of up to 42 elements. The data analysis performed was bivariate using the chi-square statistical test. The results of this study show that there is a connection between service quality and patient satisfaction. Value of the physical dimension of the p-value 0.01 (<0.05), reliability value of the p-value 0.01 (<0.05), responsiveness of the value of the p-value 0.00 (<0.05), Safety value of p-value 0.01 (<0.05) and empathy value of p-value 0.01 (<0.05). There are several aspects that do not satisfy the patient, including the unavailability of a waiting room for the patient's family. The doctor does not always do it according to the work schedule and is not on time as promised and there is no detailed description of the patient's illness. The Puskesmas are expected to expand the patient family's waiting room, provide services according to the promised time so that patients do not wait long due to the delay in service time, and more specifically ask how the patient will respond to the treatment measures as expected of the patient feels.